The Role of CXCL13 in Antibody Responses to HIV-1 Infection and Vaccination - Bekele Feyissa, Yonas; Chiodi, Francesca; Sui, Yongjun; Berzofsky, Jay A. (Frontiers in Immunology, 2021)
CXCL13 signals through the G protein-coupled chemokine receptor CXCR5 to drive development of secondary lymphoid tissue as well as B cell and Tfh cell trafficking to germinal centers (GC), which leads to the differentiation of B cells to plasma cells and memory B cells. CXCL13 has been proposed as a general plasma biomarker for GC activities. In HIV-1 infected individuals, plasma CXCL13 levels have been associated with the rate of disease progression to AIDS. Moreover, CXCL13 production has been reported to be increased in HIV-1-infected lymph nodes, which may drive increased downregulation of CXCR5. In this review, we address the role of CXCL13 in HIV-1 infected individuals with regard to GC formation, generation of broadly neutralizing antibodies after infection and vaccination, and AIDS-related B cell lymphoma.